2017
DOI: 10.1167/iovs.17-22301
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Poly-ε-Lysine Contact Lens as a Drug Delivery Device for the Treatment of Fungal Keratitis

Abstract: We demonstrated that AmpB pεK gels confer sustained therapeutic antifungal activity for at least 48 hours without corneal epithelial cell line cytotoxicity, suggesting their potential for in vivo use as an antifungal bandage contact lens. This could avoid the need for intensive topical medication in the treatment of fungal keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…A significant advantage of pεK hydrogels is that we can tailor the mechanical properties of the pεK hydrogel to fit specific requirements. In this study, a pεK hydrogel with polymer density 0.066 g/ml cross-linked to 60% with octanedioic-acid was initially used as previous research had demonstrated that this pεK hydrogel was robust enough to handle easily [38, 39]. The pεK hydrogels had a modulus of 0.11 MPa and ultimate tensile strength of 0.04 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant advantage of pεK hydrogels is that we can tailor the mechanical properties of the pεK hydrogel to fit specific requirements. In this study, a pεK hydrogel with polymer density 0.066 g/ml cross-linked to 60% with octanedioic-acid was initially used as previous research had demonstrated that this pεK hydrogel was robust enough to handle easily [38, 39]. The pεK hydrogels had a modulus of 0.11 MPa and ultimate tensile strength of 0.04 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic hydrogels are an attractive option for CE replacement as they would allow the diffusion of water and biomolecules into the stroma. Our previous studies have shown that poly-ε-lysine (pεK) cross-linked with octanedioic-acid produces hydrogels that are transparent, are non-toxic to corneal epithelial cells in vitro and can be cast into contact lens moulds [38, 39]. In addition, following crosslinking of pεK hydrogels, free amine sites remain for either electrostatic or covalent binding of drugs, proteins or peptides to the pεK hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of pɛK hydrogels (cross-linked to 60 mol% with octanedioic acid to a polymer density of 0.071 g mL −1 ), pɛK functionalization, sterilization, and wash steps were performed as previously described. 26 , 29 …”
Section: Methodsmentioning
confidence: 99%
“…The fabrication of pɛK hydrogels (cross-linked to 60 mol% with octanedioic acid to a polymer density of 0.071 g mL −1 ), pɛK functionalization, sterilization, and wash steps were performed as previously described. 26,29 Bacterial Strains and Culture Conditions P aeruginosa (PAO1) (ATCC 47085) and clinical keratitis isolates (cytotoxic strain exoU + PA39016 and invasive strain exoS + PA58017) (kindly donated by Prof. C. Winstanley, University of Liverpool, Liverpool, UK), 30 were cultured overnight on Luria-Bertani (LB) agar (Sigma-Aldrich, Dorset, UK) plates at 37°C. Five milliliters of LB broth (Sigma-Aldrich) was inoculated with bacteria and cultured for 18 hours with shaking (120 rpm/min), at 37°C.…”
Section: Pɛk Hydrogel Synthesis and Functionalizationmentioning
confidence: 99%
“…In recent years, several examples of the mentioned drugs have been incorporated into CLs using many different techniques, and the obtained results have been extensively discussed in previous review papers [21,111,186]. Therapeutic CLs for the treatment of keratitis have also been widely reported in literature reviews [187,188], with promising results for the delivery of biocides [189,190], antifungals [189,[191][192][193][194], and antiviral drugs [195,196].…”
Section: Corneal Diseasesmentioning
confidence: 99%